Economic burden of generalized pustular psoriasis and palmoplantar pustulosis in the United States. (4th May 2021) - Hanna, Maya L.; Singer, David; Valdecantos, Wendell C.
Abstract: Objective: To estimate healthcare resource utilization (HCRU) and economic burden of generalized pustular psoriasis (GPP) and palmoplantar pustulosis (PPP) in a commercially insured population the United States (US). Methods: Adult patients with a GPP or PPP diagnosis were identified between April 1, 2016 and August 1, 2019 in the IQVIA PharMetrics Plus database. Patients required continuous enrollment in medical and pharmacy benefits 6 months before and ≥2 months after the index diagnosis. GPP and PPP cohorts were exactly matched 1:3 on demographics and index date to a plaque psoriasis and a control cohort of the general population. All-cause HCRU and cost measures (direct medical and pharmacy) were reported as per patient per month (PPPM). Generalized linear models estimated adjusted cost ratios between matched cohorts, controlling for comorbidities. Results: HCRU was high among GPP and PPP patients. Rates of inpatient visits were 4 times higher in GPP patients and 2 times higher in PPP patients compared to their matched cohorts. GPP patients experienced significantly higher total healthcare costs compared to matched cohorts (GPP vs plaque psoriasis: cost ratio 1.36, 95% confidence interval (1.22, 1.50); GPP vs control: 5.58 (3.73, 8.36)). PPP patients had significantly higher total healthcare costs compared to the general population (4.11 (3.31, 5.11)), while costs were comparable to plaque psoriasis patients (1.06 (0.97, 1.16)). Conclusions: GPP and PPP patients have significant economic burden due to higher direct medical and pharmacy costs. Further investigation is needed to better understand the drivers of economic burden in patients with GPP and PPP, and how HCRU and costs are impacted by disease severity.